The Headmaster's Darlings : A Mountain Brook Novel - Clark, Katherine, 1962 November 11- (Book collections on Project MUSE., 2015)
A satirical comedy of manners featuring the morbidly obese Norman Laney, an unorthodox, inspirational English teacher and college counselor for an elite private school in Mountain Brook, a privileged community outside of Birmingham. A natural wonder from blue-collar Alabama, Laney has barged into the exclusive world of Mountain Brook on the strength of his sensational figure and its several-hundred-pound commitment to art and culture. His mission is to defeat "the barbarians," introduce true civilization in place of its thin veneer, and change his southern world for the better. Although Laney is adored by his students (his "darlings") and by the society ladies (also his "darlings") who rely on him to be the life of their parties and the leader of their book clubs, there are others who think he is a larger-than-life menace to the comfortable status quo of Mountain Brook society and must be banished.